An analysis of the level of knowledge about diabetes among pregnant women - Buraczewska, Ewelina; Sokołowska, Barbara; Mazurkiewicz, Barbara; Borzęcki, Andrzej (Family Medicine & Primary Care Review, 2016)
Background . Diabetes in pregnancy is a condition which includes pre-pregnancy diabetes in women already suffering from diabetes who become pregnant, and hyperglycaemia first diagnosed during pregnancy, defined as a disorder of carbohydrate tolerance resulting in increased blood glucose concentrations, which were first diagnosed in pregnant healthy women. Women’s knowledge about the disease and the practical use of this knowledge play an important role in the healing process. Objectives. The assessment of the state of knowledge about diabetes in pregnant women diagnosed with hyperglycaemia during pregnancy. Material and methods. The study involved 127 pregnant women with hyperglycemia which was first diagnosed during pregnancy. The median age of the subjects was 32.1 (19–45). A diagnostic survey was a research method. A self-prepared survey questionnaire was the research tool. The results were statistically analyzed. Results. The surveyed women assessed their knowledge about gestational diabetes as good and very good. The study showed, however, very poor knowledge about the clinical signs of diabetes among the subjects. The most frequently cited risk factors for gestational diabetes include: the presence of diabetes in one’s family, overweight states or obesity, and diabetes in previous pregnancy. The Internet was the main source of knowledge about diabetes among the subjects. Conclusions . 1. The level of knowledge in women about gestational diabetes is insufficient. 2. There is a need to extend educational activities related to the symptoms of diabetes and the principles of its prevention among pregnant women. 3. The participation of general practitioners in the education of women about diabetes in pregnancy is insufficient.